The Future of the Natural Gas Market in Southeast Europe - World Bank (World Bank, 2012)
The Future of the Natural Gas Market in Southeast Europe analyzes the role of natural gas in the energy mix to meet future demand in nine markets in the region: Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Kosovo, Macedonia, Montenegro, Romania, and Serbia. These markets are all signatories of the Athens Memoranda of 2002 and 2003, which commit the participants to regional cooperation in electricity and gas. Most countries heavily rely on solid fuels (such as wood and coal) or electricity (that is generated from thermal power) to meet domestic energy needs. Natural gas markets are underdeveloped or do not exist. This study identifies regional, cross-border, and country-specific gas infrastructure projects that are economically, financially, and technically sound. It makes proposals for the institutional and policy issues related to funding and implementing gas infrastructure projects. This study also examines sources of gas supply from Russia, the Caspian region, and other current and prospective producer countries through Turkey and other transit routes (including liquefied natural gas) and it assesses costs of supply and gasification prospects in Southeast Europe.